Analisis pemahaman konsep bentuk aljabar ditinjau dari gaya belajar siswa - Yuniarti, Titin; Supriyono, Supriyono; Nugraheni, Puji; Wasiman, Wasiman (Jurnal Inovasi Pendidikan Matematika (JIPM), 2020)
This study aims to describe students' understanding of solving algebraic problems with visual, auditory, and kinesthetic learning styles. This research is qualitative research with a qualitative descriptive method. The research subject was students of class VII SMP Negeri 2 Puring who had visual, auditory, and kinesthetic learning styles with 2 students' learning styles. The technique of taking the subject uses purposive. The instruments used were questionnaires and tests. This study shows that (1) Understanding the concept of restating a concept on the elements of algebraic form fulfilled by students with visual and auditory styles. (2) According to certain characteristics, classifying objects determines similar and dissimilar terms, and all student learning styles have not fulfilled its reasons. (3) providing examples and non-examples of the concept in determining similar and dissimilar tribes fulfilled by students with kinesthetic learning styles. (4) presenting concepts in various forms of mathematical representations in making all student learning styles have not fulfilled mathematical models. (5) use, utilize and select certain procedures or operations in determining operations fulfilled by all student learning styles. (6) applying the concept or problem-solving algorithm in applying the concept of algebraic forms has not been fulfilled by all student learning styles.